Effect of seed size and osmo-priming on yield and its component characters in Brassica nigra L - Raj Kumar; H Prashanth Babu (Journal of Oilseed Brassica, 2026)
Indian mustard is a major edible oilseed crop cultivated in India. Rapid seedling establishment is an important requirementfor successful crop production in wetland and dry land farming systems. Seedling establishment and speed of emergenceinfluence the time required for seedling to reach the autotrophic phase. The present investigation showed that, Seed sizediffered significantly for the traits secondary branches and days to 50% flowering and it was non-significant for othertraits. The priming treatments differed significantly for traits; days to flowering, days to 50% flowering, primary branches,secondary branches and seed yield per plant whereas, it was non-significant for other yield attributing traits. The hydropriming had a prominent effect on most of characters and is a preferable method for improving seed yield. This wasfollowed by Kcl treatment, which showed its positive effect on yield related traits like number of seeds per pod and 100seed weight. The Nacl treatment has good effect in increasing primary branches and reducing number of days requiredto flowering. Bold seed showed higher number of secondary branches, 100 seed weight and took more number of daysto first flowering and 50% days to flowering. It has been observed that the medium sized seeds gave better meanperformance for most of the traits under consideration. This was followed by small seeded ones. All the traits showedpositive correlation with yield and were non-significant, indicating that increasing seed size and seed priming producesmore seed weight.